(untitled) (Revista Argentina de Musicología, 2026)
This article examines the figure of Paul Walter Jacob as a forerunner of musical resistance against totalitarianism, drawing on the concept of the activist committed to artistic freedom during the wartime period. During his stay in Paris (1933-1934), Jacob recognized the dangers that the National Socialist regime posed to the free use of music, and argued for the need to protect it as a means of safeguarding society from totalitarian manipulation and control. These ideas anticipate and converge with the combative spirit of Charles Delaunay who, within the context of the parallel and opposing development of National Socialism and jazz culture among European youth, foresaw and evaded the restrictive measures of Nazi musical policy against so-called "degenerate" creations. At the helm of the Hot Club de France during the Occupation, Delaunay shrewdly upheld French and European identity, grounded in fraternity, freedom, and equality. Building on this convergence, the study invites reflection on musical resistance through jazz as a legitimate form of expression and social engagement, bringing into dialogue the trajectories of Jacob and Delaunay between 1933 and 1944. Editorial History: Received: April 1, 2025 Accepted: July 8, 2026